Post-transplant malignancies in solid organ recipients: development mechanisms and risk factors - A. V. Nikulin; I. V. Pashkov; Y. S. Yakunin (Вестник трансплантологии и искусственных органов)
According to the International Agency for Research on Cancer, there were an estimated 19,292,789 new cancer cases in various localizations and 9,958,133 cancer deaths worldwide in 2020. These frightening figures clearly show that malignancies among the population is a pressing matter. The risk of post-transplant malignancy in solid organ recipients is 2–6-times higher than in the general population. Given the steadily increasing number of solid organ transplants worldwide and the gradual increase in life expectancy among organ recipients, studying the issues concerning risk factors and development mechanisms becomes a crucial task.